Boson peak and nanostructure of chalcogenide glass-like semiconductors - R.I, Alekberov (JOURNAL OF ADVANCES IN PHYSICS, 2014)
The structural features of As2Se3, As40Se30S30, As40Se30Te30, As33.3Se33.3S33.4, As33.3Se33.3Te33.4 chalcogenide glasses have been studied by Raman spectroscopy in low-energy region. The results are explained in view of nanostructure of samples, i.e. by presence of heterogeneity in samples at the nanometer scale and with change their size depending on the modification of the chemical composition.